2022
DOI: 10.1111/jgh.15970
|View full text |Cite
|
Sign up to set email alerts
|

Short‐chain fatty acids affect the development of inflammatory bowel disease through intestinal barrier, immunology, and microbiota: A promising therapy?

Abstract: Intestinal metabolites are attracting increasing interest, especially more and more studies have found they are closely related to diseases. Microbial fermentation of indigestible dietary fibers in the gut produces short chain fatty acids (SCFAs) as the main product. SCFAs can exert influences on the integrity of the intestinal epithelial and mucosal barrier, immune reactions, and the diversity of microbiota in humans. Thus, alteration in SCFAs may affect inflammatory bowel disease (IBD). In IBD, SCFAs are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 76 publications
(149 reference statements)
0
15
0
Order By: Relevance
“…This finding is in line with the study which described a connection between SCFAs and IBD in various aspects such as the defensive barrier, effects on immunity, and alterations in the microbial environment. [ 31 ] This suggests that NaB may promote the integrity of the epithelial barrier, which is often compromised in IBD patients. Finally, we demonstrated that silencing of GSDMB reduced cell viability and impaired cell migration and invasion, and these effects were reversed by NaB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the study which described a connection between SCFAs and IBD in various aspects such as the defensive barrier, effects on immunity, and alterations in the microbial environment. [ 31 ] This suggests that NaB may promote the integrity of the epithelial barrier, which is often compromised in IBD patients. Finally, we demonstrated that silencing of GSDMB reduced cell viability and impaired cell migration and invasion, and these effects were reversed by NaB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic plasticity of AIEC includes the consumption of short chain fatty acids (SCFAs), 28 an important class of metabolites that is cardinal to the maintenance of intestinal homeostasis. 84 , 85 In addition to being the preferred energy source for colonocytes, 86 SCFAs lower the inflammatory tone of the gut. 84 For example, butyrate, and less efficiently propionate, can inhibit histone deacetylases promoting the differentiation of Foxp3 + T regulatory cells, known to suppress inflammation.…”
Section: Metabolic Adaptation Of Aiecmentioning
confidence: 99%
“…They modulate TJs by inducing increased expression of claudin-1 and ZO-1 and decreased expression of osmotic-promoting claudin-2, thereby affecting the gut Road barrier. 37 Sodium butyrate can enhance the intestinal epithelial barrier by regulating the activation of AMP-activated protein kinase (AMPK) and the phosphorylation of myosin II-regulated light chain (MLC2), thereby promoting TJ reorganization. 24 Another important factor for SCFAs in maintaining the epithelial barrier is hypoxia-inducible factor.…”
Section: Probiotics and Their Metabolites Enhance The Function Of Int...mentioning
confidence: 99%